Device prototype to assist hand amputees in performing administrative tasks - Dunck, Danillo Augusto de Sousa; Stoppa, Gabriel Percival; Stoppa, Marcelo Henrique (Brazilian Journal of Production Engineering, 2024)
There is a need to include people who have suffered amputation of one of their hands in the labor market, which can be facilitated by means of a device that helps perform daily activities in an office. This subject is of interest to organizations due to the legal requirements for hiring people with disabilities or because of talent retention that improvements in working conditions produces. This study presents the development of a prototype that enables hand amputees to use a mouse for computer tasks and transport boxes and light equipment. The prototype successfully enables users to manipulate a mouse and perform basic computer tasks. The prototype's design also allows for keyboard use, employing a similar lever system to activate keys. Initial observations suggest the device could enhance workplace independence for hand amputees. The prototype design was informed by the assumption that users would possess normal elbow and shoulder function or have the potential to regain these functions through physical therapy.
Keywords: Device; Administrative tasks; Assistive technology